SILVER NANOPARTICLES SYNTHESIS FROM DIFFERENT FUNGAL SPECIES AND THEIR ANTIFUNGAL EFFECT - K, Ravindra. B.; Rajasab, A. H. (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: Evaluation of antifungal activity of silver nanoparticles synthesized using different fungal species Methods: Fungus like Fusarium oxysporum, Fusarium udum, Fusarium oxysporum and Stemphylium vericans were used for the synthesis of silver nanoparticles. The synthesis was characterized using UV-vis spectroscopy, X-ray diffraction, and transmission electron microscopy. Further, the synthesized silver nanoparticles was evaluated for antimicrobial activity by well diffusion against the pathogenic fungus. Results: The present study, report on the biosynthesis and antifungal effect of silver nanoparticles (AgNPs) using fungal species such as Fusarium oxysporum, Fusarium udum, Fusarium oxysporum and Stemphylium vericans. The UV-vis absorbance maxima between 400-490 nm indicate the synthesis of nanoparticles. Further, transmission electron microscopy images shows spherical shape nanoparticles of size range (36-45 nm). Synthesized AgNPs showed active antifungal activity against the isolated plant pathogenic fungi. The study reveals the use of different fungal species for AgNPs synthesis exhibits a good antifungal effect which helps us to control pathogenic fungi in the near future. Conclusion: A simple, cost effective method was developed in the present study; the synthesized silver nanoparticles was spherical in shape of size range 36-45 nm which showed good antifungal activity. Â